2018
DOI: 10.1177/1461445618754420
|View full text |Cite
|
Sign up to set email alerts
|

‘What are you taking away with you?’ Closing radio counselling encounters by reviewing progress

Abstract: Psychological radio counselling is a relatively recent development in psychological practice, where professionals provide psychological help via mass media communication. In the media context, a professional and a help-seeker face a number of communicative challenges, one of which is to close the encounter meaningfully with regard to its counselling and radio tasks. This study explicates how radio counselling encounters can be rounded off by summarising and reviewing the progress achieved in understanding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…For example, we attended to the role of children in family therapy and identified ways in which children passively or actively resisted participation (O'Reilly & Parker, ). By drawing attention to the subtleties of the interaction, therapists can become more aware of children's attention during a session. In CA work on radio counselling, Thell and Peräkylä () attended to how such encounters were closed down, while doing therapeutic work in the public sphere. They showed that callers were asked to single out useful aspects of the encounter and noted that, by requiring the formulation of conclusions by the caller, there was a recognition of their entitlement to judge the outcomes, but also checked and reviewed the caller's understanding of the problem. In a study of Cognitive Behaviour Therapy, Antaki, Leudar, and Barnes () demonstrated that there can be resistance by a client with the therapist's formulation of the problem, and this disaffiliation asserts a position of the client's felt experience.…”
Section: What Are Useful Examples Of “Applied Ca”?mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we attended to the role of children in family therapy and identified ways in which children passively or actively resisted participation (O'Reilly & Parker, ). By drawing attention to the subtleties of the interaction, therapists can become more aware of children's attention during a session. In CA work on radio counselling, Thell and Peräkylä () attended to how such encounters were closed down, while doing therapeutic work in the public sphere. They showed that callers were asked to single out useful aspects of the encounter and noted that, by requiring the formulation of conclusions by the caller, there was a recognition of their entitlement to judge the outcomes, but also checked and reviewed the caller's understanding of the problem. In a study of Cognitive Behaviour Therapy, Antaki, Leudar, and Barnes () demonstrated that there can be resistance by a client with the therapist's formulation of the problem, and this disaffiliation asserts a position of the client's felt experience.…”
Section: What Are Useful Examples Of “Applied Ca”?mentioning
confidence: 99%
“…There • In CA work on radio counselling, Thell and Peräkylä (2018) attended to how such encounters were closed down, while doing therapeutic work in the public sphere. They showed that callers were asked to single out useful aspects of the encounter and noted that, by requiring the formulation of conclusions by the caller, there was a recognition of their entitlement to judge the outcomes, but also checked and reviewed the caller's understanding of the problem.…”
Section: What Are Us Eful E X Ample S Of "Applied C A"?mentioning
confidence: 99%